From Distance Education to e Learning: Philosophical and Design Imperatives - Venkatachary, Ranga (Proceedings of the International Conference on Networked Learning, 2002)
The questions addressed in this paper stem from the paradigm shift which engendered ‘life long’ learning. Distance Education models and e Learning practice share the philosophical framework of Open Learning. The design imperatives of e Learning have been shaped by ICT. The divergence as a design imperative is of relative significance. The principle of ‘theory neutrality’ in designing reusable learning objects is questionable from the viewpoint of instructional efficacy. The paper argues that scope and sequence are significant factors in the process of designing learning objects. They determine the bonding characteristics of the objects and thus dictate the manner of their reusability.